Temperature-selective dual radical generation from alkyl diiodide : applications to synthesis of asymmetric cabc multi-block copolymers and their unique assembly structures - Zheng, Jie (2019)
Temperature‐selective radical generation from a newly designed alkyl diiodide (I−R2−R1−I) was studied. R1−I and I−R2 had different reactivities for generating alkyl radicals in the presence of a tetraoctylammonium iodide (ONI) catalyst. Taking advantage of the temperature selectivity, we used the alkyl diiodide as a dual initiator in ONI‐catalyzed living radical polymerization to uniquely synthesize CABC non‐symmetric multi‐block copolymers. Because of their non‐symmetric structure, CABC multi‐block copolymers form unique assemblies, that is, Janus‐type particles with hetero‐segment coronas and flower‐like particles with hetero‐segment petals.